2013
DOI: 10.1093/aje/kwt232
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease and Cancer: A Register-based Family Study

Abstract: We wanted to compare cancer incidence rates between Parkinson's disease (PD) patients and persons without PD, as well as between siblings of these groups. We conducted a family-based matched cohort study based on nationwide Swedish health registries and the Swedish Multi-Generation Register. We assessed risk of incident cancer in PD patients (n = 11,786) during 1964-2009 versus a matched cohort of PD-free individuals (n = 58,930) and in siblings of PD patients (n = 16,841) versus siblings of PD-free individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
52
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 17 publications
8
52
2
1
Order By: Relevance
“…A Danish cohort study of 14,088 PD patients [16] and a case-control study of 8,090 Danish PD cases [17] also reported a positive association with ORs of 1.25 and 1.26, respectively. A positive relationship between PD and subsequent NMSCs was also reported in later studies [7, 18, 19], with point estimates ranging between 1.29 and 1.81 [1]. …”
Section: Discussionsupporting
confidence: 69%
“…A Danish cohort study of 14,088 PD patients [16] and a case-control study of 8,090 Danish PD cases [17] also reported a positive association with ORs of 1.25 and 1.26, respectively. A positive relationship between PD and subsequent NMSCs was also reported in later studies [7, 18, 19], with point estimates ranging between 1.29 and 1.81 [1]. …”
Section: Discussionsupporting
confidence: 69%
“…Thus, our estimates are less likely to be affected by outcome misclassification and potential (negative) confounding by smoking than the previous study. In our study, we observed positive association for malignant melanoma, which was in line with previous studies [6,8,12]. Positive associations have been reported in previous Danish registrybased studies for breast cancer [32,33], opposite to what we saw in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Since then, further evidence accumulated from case series [2][3][4] and epidemiological studies [5][6][7][8][9][10][11][12] that cancer is rarer among PD patients compared with the general population except for melanoma and perhaps breast cancer. Cancer and PD have been attributed to distinct and opposing biological mechanisms with the former being characterized by uncontrolled cell proliferation, and the latter by abnormal neuronal cell loss that occurs progressively [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two subsequent studies (9,10) showed that the PD susceptibility loci and PDspecific single nucleotide polymorphisms, identified in genomewide association studies, neither play a role in melanoma development nor contribute to the association between PD and melanoma. Likewise, a family-based matched cohort study, conducted in Sweden, ruled out familial genetic factors as the reason for the association between PD and melanoma (11).…”
mentioning
confidence: 99%